(3GdeYQHs - (3ehghH Hf CMeO Hf eMeO Hf GdNVQ Hf GdMSf, CHh GdefUhQ GHf GdLhGdjbj,J (B540 (3g` s
(3ChdgG (B:s
(3gPG cJGH fPcQ ajg eG JcdeJ Hg GdYQH ef GdcdGe GdCYLei hfWb Hg GdbQBf GdeLjO hhQO ai CNHGQ GdQShd Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3abdJ cja Jbhd ddEKfjf hGdLeY GdeDfK ade jOQ bGd CHh MGJe CXf CUdg HGdSQjGfjI jG gjG TQ CgjG Je GdcJGH s
(3eG JcdeJ Hg GdYQH ef GdcdGe GdCYLeis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B53s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1739s
Keywords: (3GddZIs